BIMBINGAN TERAPI SYUKUR PADA JEMAAH UMRAH UNTUKMENINGKATKAN ADVERSITY QUOTIENT PADA PT KARYA IMTAQ TOUR & TRAVEL - Firmansyah, Irfan; Solahudin, Dindin; Miharja, Sugandi (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This study aims to explore the experiences of umrah pilgrims participating in a guidance program that integrates gratitude therapy and to examine its impact on the Adversity Quotient (AQ). Using a qualitative approach with a phenomenological method (Creswell, 2014), data were collected through in-depth interviews with pilgrims who attended the umrah guidance program at PT Karya Imtaq. The analysis focused on participants’ narratives to uncover meanings, behavioral changes, and post-umrah strategies for maintaining gratitude. The findings reveal three main meanings of gratitude therapy: (1) a shift from reactive gratitude to proactive gratitude, (2) transformation in decision-making and attitudes toward trials, and (3) enhanced perseverance and mental resilience. Gratitude therapy positively influenced the four dimensions of AQ: control, ownership, reach, and endurance. Pilgrims reported greater emotional self-control, a stronger sense of responsibility, the ability to limit the negative impact of problems, and the belief that difficulties are temporary. The study affirms a correlation between gratitude therapy and AQ within the Islamic spiritual framework, suggesting that gratitude-based guidance strengthens spiritual, mental, and emotional resilience in facing life’s challenges.